Survival Patterns of COVID-19 Pneumonia Patients with False-Negative PCR Results Transferred to the Intensive Care Unit from the Emergency Department - Kodik, Meltem Songur; Ozturk, Esin; Altunci, Yusuf Ali; Ozcete, Enver; Yalcinli, Sercan; Ersel, Murat; Akyol, Deniz; Bayraktaroglu, Selen; Goksel, Ozlem; Celik, Ahmet Enes (Archives of Clinical and Biomedical Research, 2022)
Aim: This study aimed to analyze factors associated with patient mortality in COVID-19 patients hospitalized in the intensive care unit (ICU) and provide data to help prioritize the most critical patients. Methods: A clinical retrospective cohort study was conducted in a tertiary hospital. Patients (n=289) with negative reverse transcription-polymerase chain reaction (RT-PCR) and a positive chest computed tomography (CT) scan indicating COVID-19 were included in the research. Demographics, clinical characteristics, treatment modalities, and length of hospital stay were analyzed in relation to 30-day survival outcomes. Results: The mean age of the patients was 69.04 ± 15.10 years (range 19-100), and 41.2% (n=119) were female. The mortality rate was 48.1% (n=139). There were statistically significant differences in laboratory findings, such as hemoglobin (p=0.021), lymphocyte counts (p=0.046), d-dimer (p=0.009), and lactate (<0.001) regarding one-month survival. Additionally, those hospitalized for more than 5 days had higher one-month survival rates (hazard ratio (HR)= 0.003, CI= 10.264-155.972). Moreover, intubated patients had a higher mortality risk during this period (HR=4.15, CI=1.53-11.20). Conclusion: The first five days of patients hospitalized in intensive care units due to COVID-19 pneumonia are critical. Besides, the need for intubation was another factor independently affecting survival. Clinicians should be alerted about the significance of these factors.